Caracterização físico-química e bioativa do óleo e da manteiga de cacay (Caryodendron orinocense Karst.) e avaliação do efeito indutor na produção de lipase - Azevedo, Wendell Medeiros de (2020)
The cacay (Caryodendron orinocense Karst.) is a typical Amazonian tree that presents a nutritional composition rich in polyunsaturated fatty acids and antioxidant compounds. However, its bioactive properties and lipid inducing potential are poorly studied. Thus, the present study aims to evaluate the fatty acids profile, physicochemical, and bioactive properties of cacay oil and butter and coconut oil (cocos nucifera) as the potential inducer to lipase production from Aspergillus terreus NRRL - 255 by solid state fermentation (SSF). Initially, the fatty acids profile by gas chromatography and physicochemical characterization were performed, as well as the determination of antioxidant capacity and antibacterial activity in vitro. In addition, agro-industrial wastes were characterized for use as non-inert solid supports by SSF. The potential of the lipid inducer for fungal lipase production was also evaluated, and the lipase production process was optimized by experimental design. Finally, the lipases produced were characterized by the influence of pH, temperature, metal ions, and surfactants. Regarding the fatty acids profile and physicochemical characterization, cacay oil presents a high content of polyunsaturated fatty acids (58.32%) and a high unsaturation (116.35 cg I2.g-1 ). In contrast, cacay butter and coconut oil have greater stability against lipid peroxidation (7.77 and 5.99 meq.kg -1 ) and a high saturated fatty acid (69.09% and 78.4%), respectively. The hydrophilic fraction of cacay oil was highlighted in the quantification of total phenolic compounds (326.27 mg GAE.kg-1 ) and antioxidant capacity in vitro (156.57 μM TE.g-1 ), by DPPH radical scavenging assay. The cacay oil showed antibacterial activity against gram-positive bacteria Bacillus cereus (44.99%), Enterococcus faecalis (27.76%), and Staphylococcus aureus (11.81%). Regarding lipase production, the present study found favorable results for wheat bran as a non-inert solid support, such as the high water absorption index (3.65 g H2O.g-1 ) and, as the best lipid inducer, cacay butter, with a lipolytic activity of 308.14 U.g - 1 . After assessing lipase production by 2 5-1 fractional factorial design, the effects of temperature and time factors were considered statistically significant and optimized by 2 2 central rotational composite design, being possible to find the critical value of 27.36 °C for temperature and maximum activity of 2,867.18 U.g -1 . Regarding the characterization of the lipase, a maximum relative activity was observed at pH 7.0 and temperature of 35 ºC and an inhibitory effect was found for Ca2+, Mn2+, Zn2+, Fe2+ , and Cu2+ ions. An increase of lipase activity was found with the reduction of sodium dodecyl sulfate (SDS) concentration and increase of Triton X-100. Finally, cacay oil presented bioactive properties which might justify its industrial exploitation. On the other hand, the use of cacay butter as a lipid inducer showed a high lipolytic activity, indicating a potential biotechnology to produce industrial lipases.